Influence of Fear-Avoidance Beliefs on Disability in Patients With Subacromial Shoulder Pain in Primary Care: A Secondary Analysis. Issue 12 (1st December 2014) - Kromer, Thilo O.; Sieben, Judith M.; de Bie, Rob A.; Bastiaenen, Caroline H.G.
Abstract : Background: Little information exists about the role of fear-avoidance beliefs and catastrophizing in subacromial pain syndrome. Objective: The purpose of this study was to investigate the associations among pain, catastrophizing, fear, and disability and the contribution of fear-avoidance beliefs to disability at baseline and at 3-month follow-up. Design: A cross-sectional and longitudinal analysis was conducted. Methods: Baseline demographic and clinical data, including fear-avoidance beliefs and catastrophizing, of 90 patients were assessed for this analysis. Disability was measured with the Shoulder Pain and Disability Index at baseline and at 3-month follow-up. First, bivariate and partial correlations were calculated among pain, fear-avoidance beliefs, catastrophizing, and disability, based on the fear-avoidance model. Second, the contribution of fear-avoidance beliefs to disability at baseline and at 3-month follow-up was examined with hierarchical regression analyses. Results: Correlations between clinical variables and disability were largely in line with the fear-avoidance model. Regression analyses identified a significant contribution of fear-avoidance beliefs to baseline disability but not to disability at 3 months. Limitations: Patients with subacromial pain syndrome were studied; therefore, the results should be transferred with caution to other diagnoses. A modified version of the Fear-Avoidance Beliefs Questionnaire was used, which was not validated for this patient group. Conclusions: Fear-avoidance beliefs contribute significantly to baseline disability but not to disability change scores after 3-month follow-up. Duration of complaints and baseline disability were the main factors influencing disability change scores. Although the results help to improve understanding of the role of fear-avoidance beliefs, further studies are needed to fully understand the influence of psychological and clinical factors on the development of disability in patients with subacromial shoulder pain.